100 students celebrate World Ozone Day - Mimi Rabita, Abdul Wahit (2020)
Pekan, 17 September 2020 - More than 100 students of Universiti Malaysia Pahang (UMP) joined the Pahang State Ozone Layer Protection Awareness Programme in conjunction with the World Ozone Day 2020 annually celebrated on 16 September.